Anthropology and Hebrew Bible Studies Modes of Interchange and Interpretation - Goldberg, Harvey E. 1939- (2018)
Interaction between anthropology and biblical scholarship began because of perceived similarities between “simpler” societies and the practices and ideas seen in the Bible. After some disengagement in the first half of the twentieth century, new cross-disciplinary possibilities were envisioned as the structuralist approach emerged in anthropology. Ritual and mythology were major topics that received attention and structuralist methods were partially adopted by some biblical scholars. Anthropological research itself extended to complex societies and also affected historical studies, yielding models of inquiry that engaged a range of disciplines. Among the issues explored in this essay are ritual and notions of purity in the Bible, and the place of literacy in Israelite society and culture. These discussions are followed by three examples of structuralist-inspired analysis that partially take into account historical and literacy-based facets of the Bible.